Pengaruh Disiplin Kerja, Motivasi Kerja dan Lingkungan Kerja terhadap Kinerja Guru UPT SMP Negeri 11 Gresik - Fitri Sintia Yulia Ningsih; Roziana Ainul Hidayati (Universitas 45 Surabaya, 2024)
This Based on the research results, the performance of UPT teachers at SMP Negeri 11 Gresik is less than optimal, which can affect work discipline, which can be seen from the recap of teacher absences, many teachers give permission during the teaching and learning process, and in teaching there are teachers who only give assignments after which they are left alone. just without supervision. And the work environment at UPT SMP Negeri 11 Gresik is still lacking in supporting the teaching and learning process between teaching staff and students, such as: a lack of LCD projectors in each room, and the work space for teaching staff is not well lit, the layout of office desks between teaching staff is also does not have partitions and there is a lack of air conditioning in the classroom. The aim of this research is to analyze whether there is a partial influence of work discipline, work motivation and work environment on the performance of teachers at UPT SMP Negeri 11 Gresik. The number of samples used in this research was 39 respondents, the method used was the Saturated Sampling method. The data analysis technique using multiple linear regression analysis proves that the work discipline and work environment variables have no effect, while work motivation has a significant effect on the performance of teachers at UPT SMP Negeri 11 Gresik.